Rotavirus disease and health care utilisation among children under 5 years of age in highly developed countries: A systematic review and meta-analysis. Issue 22 (21st May 2021) - Ardura-Garcia, Cristina; Kreis, Christian; Rakic, Milenko; Jaboyedoff, Manon; Mallet, Maria Christina; Low, Nicola; Kuehni, Claudia E.
Abstract: Background: Rotavirus (RV) infection is the leading cause of diarrhoea‐associated morbidity and mortality globally among children under 5 years of age. RV vaccination is available, but has not been implemented in many national immunisation plans, especially in highly developed countries. This systematic review aimed to estimate the prevalence and incidence of health care use for RV gastroenteritis (RVGE) among children aged under 5 years in highly developed countries without routine RV vaccination. Methods: We searched MEDLINE and Embase databases from January 1 st 2000 to December 17 th 2018 for publications reporting on incidence or prevalence of RVGE‐related health care use in children below 5 years of age: primary care and emergency department (ED) visits, hospitalisations, nosocomial infections and deaths. We included only studies with laboratory‐confirmed RV infection, undertaken in highly developed countries with no RV routine vaccination plans. We used random effects meta-analysis to generate summary estimates with 95% confidence intervals (CI) and prediction intervals. Results: We screened 4033 abstracts and included 74 studies from 21 countries. Average incidence rates of RVGE per 100 000 person‐years were: 2484 (95% CI 697‐5366) primary care visits, 1890 (1597‐2207) ED visits, 500 (422‐584) hospitalisations, 34 (20–51) nosocomial infections and 0.04 (0.02–0.07) deaths. Average proportions of cases of acute gastroenteritis caused by RV were: 21% (95% CI 16‐26%) for primary care visits; 32% (25‐38%) for ED visits; 41% (36‐47%) for hospitalisations, 29% (25–34%) for nosocomial infections and 12% (8–18%) for deaths. Results varied widely between and within countries, and heterogeneity was high (I 2 > 90%) in most models. Conclusion: RV in children under 5 years causes many healthcare visits and hospitalisations, with low mortality, in highly developed countries without routine RV vaccination. The health care use estimates for RVGE obtained by this study can be used to model RV vaccine cost-effectiveness in highly developed countries.